2012
DOI: 10.4103/2230-8210.102995
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profile and cardiovascular risk factors in adult patients with congenital adrenal hyperplasia due to 21-hydroxylase deficiency

Abstract: Background:In congenital adrenal hyperplasia (CAH), long-term glucocorticoid treatment coupled with increased androgens may lead to undesirable metabolic effects. The aim of our report was to determine the prevalence of metabolic abnormalities and cardiovascular risk factors in a population of adult patients with CAH due to 21 hydroxylase deficiency.Materials and Methods:Twenty-six patients (11 males and 15 females, mean age ± SD=27.4±8.2 years) were recruited. Anthropometry, body composition, metabolic parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Ultrasound assessment of cIMT is a well-established examination that perfectly correlates with CV risk estimated by means of Systematic COronary Risk Evaluation (SCORE scale), which is the perfect tool for predicting the risk of CV death [27]. The present study revealed increased cIMT and fIMT in CAH patients, similarly to other results [3,11,12], but after correction for classic CVD risk factors and substitution doses of steroids the value was not statistically important. This reveals the possible relationship between IMT and glucocorticoid replacement therapy.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Ultrasound assessment of cIMT is a well-established examination that perfectly correlates with CV risk estimated by means of Systematic COronary Risk Evaluation (SCORE scale), which is the perfect tool for predicting the risk of CV death [27]. The present study revealed increased cIMT and fIMT in CAH patients, similarly to other results [3,11,12], but after correction for classic CVD risk factors and substitution doses of steroids the value was not statistically important. This reveals the possible relationship between IMT and glucocorticoid replacement therapy.…”
Section: Discussionsupporting
confidence: 66%
“…It has been described that adolescent children with CAH present vascular dysfunction measured by flow-mediated dilatation of the brachial artery (FMD) and increased carotid intima media thickness (cIMT) [8][9][10][11]. cIMT remains higher in adults [3,12]. The echocardiographic changes in young patients with CAH have been poorly described; there is only limited information concerning the increase of the left ventricular mass index (LVMI) and left ventricular (LV) dysfunction compared with controls [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…This is why the American Heart Association recommends it as a non-invasive imaging study to detect atherosclerosis [ 30 ]. In our study, the CIMT was only non-significantly higher in patients with CAH, where more than half showed increased thickness (> 90th percentile), which is an indication of a subclinical atherogenic process [ 31 ]. The associations between CIMT and 17OHP levels, diastolic blood pressure and the HOMA index were striking and have been shown by others as well [ 27 ].…”
Section: Discussionmentioning
confidence: 95%